2019
DOI: 10.5114/jcb.2019.88762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deformable image registration algorithm for determination of accumulated dose for brachytherapy of cervical cancer patients

Abstract: PurposeThis study was designed to assess the dose accumulation (DA) of bladder and rectum between brachytherapy fractions using hybrid-based deformable image registration (DIR) and compare it with the simple summation (SS) approach of GEC-ESTRO in cervical cancer patients.Material and methodsPatients (n = 137) with cervical cancer treated with 3D conformal radiotherapy and three fractions of high-dose-rate brachytherapy were selected. CT images were acquired to delineate organs at risk and targets according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…ABAS algorithms use deformable image registration to transform OAR contours from the atlas into the new image. There is a lack of certainty in deformable registration algorithms [15][16][17], particularly when intensity-based algorithms are used. In addition, there are a number of issues that must be considered when using ABAS since there is a large variability in the pelvic region owing to internal organs motion, bladder filling, and presence of gas in the rectum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ABAS algorithms use deformable image registration to transform OAR contours from the atlas into the new image. There is a lack of certainty in deformable registration algorithms [15][16][17], particularly when intensity-based algorithms are used. In addition, there are a number of issues that must be considered when using ABAS since there is a large variability in the pelvic region owing to internal organs motion, bladder filling, and presence of gas in the rectum.…”
mentioning
confidence: 99%
“…In addition, there are a number of issues that must be considered when using ABAS since there is a large variability in the pelvic region owing to internal organs motion, bladder filling, and presence of gas in the rectum. These factors result in sub-optimal performance of ABAS, in particular when a small number of atlases (typically [10][11][12][13][14][15][16][17][18][19][20] are used [18][19][20][21]. Moreover, the presence of applicators and CT markers for brachytherapy implantation tends to decrease contrast to noise ratio and to increase high-density…”
mentioning
confidence: 99%
“…Therefore, to map BRT doses in the bladder visualized in CT images (EBRT), advanced image registration methods need to be applied. For the sake of clinical utility, it is important to measure the error caused by those transformations., and for that reason, the present study did not raise issues related to combining doses deposited in particular BRT fractions [21] or combining doses between BRT and EBRT [5]. The study only evaluated the accuracy of image registration and dose-based transformations performed.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual phantoms were generally preferred for verification. Mohammadi et al [38] evaluated hybrid-based DIR algorithm using a virtual phantom, and demonstrated a low registration uncertainty for both contour matching and dose mapping. On the other hand, DIR is particularly challenging in the pelvic region due to large and complex deformations caused by organ motions, applicator displacement, and differences in the rectum and bladder filling [23,28,39].…”
Section: Discussionmentioning
confidence: 99%